Is the Term “Food Consistency” Used Consistently in Consumer Science? An Exploratory Study of Consumer Association and Conceptualization - Della Fontana, Franco Darío (2024)
The post-pandemic context has changed the modes for collecting data in sensory and consumer science. The objectives of this research were to analyse consumers’ associations of food consistency and to study two virtual modes of the Free Word Association test (FWA). This test was administered to 209 consumers (180 women, 29 men, 18-45 years old) asynchronously (i.e. self-administered) and synchronously (i.e. face to face interviews). The Cognitive Salience Index (CSI) was calculated, and the structure of the social representation was analysed. Correspondence analysis showed that food consistency was a mixture of concepts related to structure, hardness and several aspects of auditory (e.g. Crunchy, Crispy), tactile (e.g. Smooth, Spreadable), and oral texture (e.g. Creamy, Gummy). Slightly consistent food was associated with something soft, liquid or semisolid, and very consistent food to something hard and resistant. Consistent food was more related to “very” than to “slightly consistent”. The CSI depended on the stimulus presented (p<0.05). Regarding the social representation structure, the central core had the highest CSI for all stimuli (CSI ≥ 0.13, p<0.05). Consumers defined “very consistent, consistent and slightly consistent food” by naming more foods in the synchronous mode than in the asynchronous one. In the asynchronous mode, consumers took more time to complete the test. The virtual FWA test (asynchronous or synchronous) showed some differences in the associations of term consistency, due to the lack of spontaneity in the first minute. It is important to adjust the methodologies to standardize the times in both modes.